Genome-wide Association Study of Birth Weight in Bali Cattle (Bos javanicus) - P. Sudrajad; H. Suhada; D. Prasetyo; P. N. Gariri; E. Eddianto; A. F. Abiyoga; R. Y. Kusminanto; S. Sukaryo; T. A. Bramastya; S. D. Volkandari; M. Cahyadi (Tropical Animal Science Journal, 2023)
The genome-wide association study is popularly used to identify markers associated with high economic traits in cattle breeds worldwide. However, this method has never been applied to Bali cattle (Bos javanicus), which are indigenous to Indonesia. Therefore, this study aimed to determine whether the GWAS can also be employed to figure out genomic regions potentially affecting Bali cattle's birth weight trait. In this study, phenotypic and genotypic data of 48 Bali cattle were used to figure out genomic regions which are potentially affecting the birth weight trait of Bali cattle. Those samples were genotyped using an Illumina bead chip array with 53.218 single nucleotide polymorphisms (SNPs). The estimation of the variance proportion explained by each SNP was conducted by a restricted maximum likelihood (REML) approach. The result showed that the birth weight trait in Bali cattle was affected by multiple regions dispersed over the genome, especially chromosomes 20 and 21. This study demonstrated that GWAS can be used effectively and discovered two intriguing regions related to quantitative trait loci and genes, namely STXBP6 and TERT, which previously had been linked to cattle birth weight and growth. These findings are important for developing and refining genomic-based selection programs for Bali cattle in Indonesia.